Entrenamiento metacognitivo y ganancias significativas de los alumnos en algunas variables cognitivas y pedagógicas. Un estudio en la educación primaria y secundaria obligatoria (6º, 7º y 8º de EGB) de Andalucía, Cantabria y Galicia - Talavera., Elvira Repetto (Revista Española de Pedagogía, 2025)
Nowadays, it is more and more frequent to find research on metacognitive strategies. In this article we present an experimental study about the student significative gains on some pedagogical and cognitive variables after implementing, the Repetto’s Metacognitive Reading comprehension program (OMECOL). After reviewing some of the main theoretical foundations, we centre our attention on the description of strategies for promoting reading comprehension and on the MANCOVA student gains on several learning products and cognitive variables.